Learning Theories: From Divine to Mortals - Ahmed Badar (Journal of University College of Medicine and Dentistry)
Learning is a fascinating journey, a puzzle waiting to be solved. It's like piecing together a complex jigsaw, with each theory offering a unique piece of the puzzle. As an educator, I've come to appreciate three fundamental learning theories that have shaped the way we understand the process of acquiring knowledge: Behaviorism, Cognitivism, and Constructivism.